Chronologic versus Biologic Aging of the Human Choroid - Christian Albrecht May (The Scientific World Journal)
Several aspects of chronologic and biologic aging in the human choroid are reviewed from the literature. They often reveal methodological problems for age-dependent changes of the following parameters: choroidal thickness, choroidal pigmentation, choroidal vasculature and blood flow, and choroidal innervation. On reinterpreting some data of studies concerning Bruch’s membrane, changes observed at different age points seem more likely to be nonlinear. Concluding from the data presented so far, chronologic aging should not be used as a factor for physiological changes in the human choroid. Longitudinal study designs are necessary to further establish the impact of age. Meanwhile, a more biologic oriented model of aging processes in the choroid should be established, including specified conditions (e.g., light exposure and refractory state). This would help to define more individual strategies for prevention and early stages of a certain defined disease.